Potensi Beberapa Isolat Probiotik Sebagai Antibakteri Terhadap Pertumbuhan Vibrio spp. - ZARASWATI DWYANA; NUR HAEDAR; HASBIAH HASBIAH (Prosiding Seminar Biologi, 2016)
The research about potential of some probiotic isolates as an antibacterial on the growth of Vibrio spp had been done. This research aimed to know the antibacterial potency from some isolates probiotic on the growth of Vibrio spp. This research to tested the inhibition on the three species of Vibrio that are Vibrio harveyi, Vibrio prahaemolyticus, and Vibrio cholerae using agar diffusion method. Probiotic isolates come from lactic acid bacteria group that provide beneficial effects on health and its host. Used also commercial probiotic (S.NB) as a positive control. From the results of the inhibitory effect on the growth of pathogenic bacteria test showed all isolates probiotics have the ability to inhibit Vibrio spp. At 1 x 24-hour observation shown isolates B most excellent in inhibiting the growth of Vibrio harveyi, against Vibrio parahaemolyticus obtained isolates C most excellent inhibited bacteria, whereas against Vibrio cholerae isolates H was most excellent in inhibiting the pathogenic bacteria. After 2 x 24 hours observation was to known that all isolates probiotics used have the ability as antibacterial that was bactericidal on the growth of Vibrio harveyi, Vibrio parahaemolyticus and Vibrio cholera.  Keywords: Antibacterial, Probiotic Isolates, Vibrio spp